GAYA KEPEMIMPINANDALAM MENINGKATKAN KINERJA STAF BALAI REHABILITASI SOSIAL ANAK YANG MEMERLUKAN PERLINDUNGAN KHUSUS (BRSAMPK)” RUMBAI” PEKANBARU - Nababan, Kertina; Jas, Jasfar; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Based on interviews with some of the Social Rehabilitation Center Staff Children in Need of Special Protection (BRSAMPK) Jalan Rumbai Coastal School, Rumbai Beach, Pekanbaru, did not pay much attention to the dynamics and performance of staff in running the program, often authoritarian, unwilling to know, such as not accepting the opinions of subordinates, not responding the opinions of his subordinates. This type of research used in this research is descriptive using a quantitative approach. According to Sugiyono (Sugiyono: 2014: 49) This descriptive research aims to provide a systematic description of the situation that occurs in the research project, Leadership Style in Improving the Performance of Staff of the Social Rehabilitation Center for Children Needing Special Protection (BRSAMPK) "Rumbai" Pekanbaru. The population in this study were all staff members of the Children's Social Rehabilitation Center Needing Special Protection (BRSAMPK) Pekanbaru "Rumbai" with a total of56 people. Based on data analysis and research results, it was concluded that the leadership style of the head of the Social Rehabilitation Center Staff Needs Special Protection "Tassel" ie. The highest leadership style is the Democratic leadership style with the acquisition of an average percentage value (SS + S) of 74.6%. That the democratic leadership style indicator is seen from the average response of respondents is quite good, because according to BRSAMPK Staff, it was found that the coordination of leaders, members participated more than leaders, rather than leaders, before making decisions first members asked for opinions of leaders.KeyWords: Leadership Style, Staff Performance